Let the dead sleep - Graham, Heather (Graham, Heather. Cafferty & Quinn novel., 2013)
A centuries-old bust of an evil, demonic man was stolen from a New Orleans grave. Its current owner shows up at Danni Cafferty's antiques shop, but before Danni can buy the statue, it disappears and the owner is found dead. Michael Quinn, a private investigator, believes that the right thing to do is to find and destroy this object weighted with malevolent powers. He and Danni follow it through sultry nights to hidden places in the French Quarter and secret ceremonies on abandoned plantations.